Prognostic factors for clinical outcomes after rotator cuff repair - Pécora, José Otávio Reggi (Acta Ortop Bras, 2015)
OBJECTIVE: To identify prognostic factors of postoperative functional outcomes. METHODS: Retrospective case series evaluating patients undergoing rotator cuff repair, analyzed by the UCLA score (pre and 12-month postoperative) and Magnetic Resonance Imaging (preoperative). Patients' intrinsic variables related to the injury and intervention were evaluated. Multivariate linear regression analysis was performed to determine variables impact on postoperative functional assessment. RESULTS: 131 patients were included. The mean UCLA score increased from 13.17 ± 3.77 to 28.73 ± 6.09 (p<0,001). We obtained 65.7% of good and excellent results. Age (r= 0.232, p= 0.004) and reparability of posterosuperior injuries (r= 0.151, p= 0.043) correlated with the functional assessment at 12 months. After multivariate linear regression analysis, only age was associated (p = 0.008). CONCLUSIONS: The surgical treatment of rotator cuff tears lead to good and excellent results in 65.6% of patients. Age was an independent predictor factor with better clinical outcomes by UCLA score in older patients. Level of Evidence IV, Case Series.